Estudio comparado y sociojurídico de la unión de hecho desde el caso ecuatoriano con los países de América Latina y/o la Unión Europea - Fabiani Orbea, Bremero Leonardo (2018)
Resumen:The present study focused on analyzing the legislation of Ecuador and Uruguay from the sociolegal context of the Unión de Hecho. The purpose of the normative comparison with Uruguayan regulations was to determine similarities and differences between their regulations. For this, theoretical postulates have been established that guided the study. In the field research, 32 surveys were applied to lawyers in free professional practice, in order to strengthen the analysis, reviewing two case studies that allowed understanding the particularities with which the rule resolves the entire legal context that the Union de Hecho presents in the country.